The Levy Institute Measure of Economic Well-Being, France, 1989 and 2000 - Thomas Masterson; Ajit Zacharias; Selçuk Eren; Edward N. Wolff (Levy Economics Institute of Bard College, 2011)
We construct estimates of the Levy Institute Measure of Economic Well-Being for France for the years 1989 and 2000. We also estimate the standard measure of disposable cash income (DI) from the same data sources. We analyze overall trends in the level and distribution of household well-being using both measures for France as a whole and for subgroups of the French population. The average French household experienced a slower rate of growth in LIMEW than DI over the period. A substantial portion of the growth in well-being for the middle quintile was a result of increases in net government expenditures and income from wealth. We also found that the well-being of families headed by single females relative to married couples deteriorated much more, while the well-being of households headed by the elderly relative to households headed by the nonelderly improved much more than indicated by the standard measure of disposable income. The conventional measure indicates that a steep decline in economic inequality took place between 1989 and 2000, while our measure indicates no such change. We argue that these outcomes can be traced to the difference in the treatment of the role of wealth in shaping economic inequality. Our measure also indicates that, on balance, government expenditures and taxes did not have an inequality-reducing effect in France for both years. This is, again, contrary to conventional wisdom.
Keywords: D31; D63; P17; 330; Levy Institute Measure of Economic Well-Being (LIMEW); France; economic well-being; economic inequality; household income measures